ANALYSIS OF FINANCIAL DISTRESS USING THE ALTMAN Z-SCORE AND TAFFLER METHODS IN CEMENT SUBSECTOR MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2018-2021 - Anwar; Puspita K, Armita; Muh. Ichwan Musa; Romansyah Sahabuddin; Anwar Ramli (CV. Radja Publika, 2023)
This research aims todetermine the potential for Financial Distress in cement manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The equation model used is the Altman Z-Score and the Taffler model. The data collection technique used is the documentation method with quantitative descriptive research data types. The results of the study show that cement sub-sector manufacturing companies for the 2018-2021 period have varied analysis results depending on the type of model implementation used. Companies that are in a healthy condition (safe area) for the two equation models are INTP in 2018-2021, and SMBR in 2018 for the Altman Z-Score model, while the SMGR Taffler model in 2018 is in a healthy condition (safe area). SMGR 2018-2020, WSBP 2018-2019, WTON 2018, and SMBR for 2020-2021 is in a gray area position for the Altman Z-Score equation model. While in the taffler model, companies that are in a gray area position are SMGR in 2019-2021, SMCB 2019-2020, WSBP in 2021, and SMBR in 2018 and 2021. Meanwhile companies that are in a bankrupt position are SMGR in 2021, SMCB in 2018- 2021, 2019-2020 WSBP, 2019-2021 WTON and 2019 SMBR for the Altman Z-Score model. In the taffler model, bankrupt companies are 2018 and 2021 SMCB, 2020 WSBP, and 2019-2020 SMBR. 2019-2020 WSBP, 2019-2021 WTON and 2019 SMBR for the Altman Z-Score model. In the taffler model, bankrupt companies are 2018 and 2021 SMCB, 2020 WSBP, and 2019-2020 SMBR. 2019-2020 WSBP, 2019-2021 WTON and 2019 SMBR for the Altman Z-Score model. In the taffler model, bankrupt companies are 2018 and 2021 SMCB, 2020 WSBP, and 2019-2020 SMBR